2003
DOI: 10.1271/bbb.67.1048
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Agar-degradingPaenibacillusspp. Associated with the Rhizosphere of Spinach

Abstract: Agar-degrading bacteria in spinach plant roots cultivated inˆve soils were screened, and four strains of Paenibacillus sp. were isolated from roots cultivated in three soils. The agar-degrading bacteria accounted for 1.3z to 2.5z of the total bacteria on the roots. In contrast, no agar-degrading colony was detected in any soil (non-rhizosphere soil samples) by the plate dilution method, and thus these agar-degrading bacteria may speciˆcally inhabit plant roots. All isolates produced extracellular agarase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 43 publications
1
44
0
4
Order By: Relevance
“…This microorganism has the ability to completely decompose plant material due to a multi-enzyme system, which allows at least ten different polysaccharides, including agar, to degrade the plant to its elemental or sugar derivatives (Shin et al 2009). Most of the isolated and characterized agarolytic enzymes have a maximum activity at temperatures above 30°C (Hosoda et al 2003;Fu and Kim, 2010). Pseudoalteromonas antarctica with agarolytic activity was described by Vera et al (1998) from decomposing algae found on the coast of Valdivia (Chile).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This microorganism has the ability to completely decompose plant material due to a multi-enzyme system, which allows at least ten different polysaccharides, including agar, to degrade the plant to its elemental or sugar derivatives (Shin et al 2009). Most of the isolated and characterized agarolytic enzymes have a maximum activity at temperatures above 30°C (Hosoda et al 2003;Fu and Kim, 2010). Pseudoalteromonas antarctica with agarolytic activity was described by Vera et al (1998) from decomposing algae found on the coast of Valdivia (Chile).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ability to degrade complex sugars by specific enzymes has been reported as a characteristic of some algae-associated epiphytic bacteria (Hosoda et al 2003;Fu and Kim 2010). In literature, several examples can be found, like the marine bacterium Saccharophagus degradans, which was isolated from decomposing Spartina alterniflora, found in estuaries (Ekborg et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a number of microorganisms have been reported to secrete agarase, mainly in a marine environment, either in the sea water, in marine sediments or associated to red algae [4,5]. The agarase producing bacteria are also isolated from nonmarine environments, like the ones from low-land river [6], soil [7,8] and plant root [9]. There are limited number of studies which have investigated the optimization of culture conditions for agarase-producing microbes [10][11][12][13][14][15][16].…”
Section: International Letters Of Natural Sciencesmentioning
confidence: 99%
“…Agarose, the main constituent, is a neutral polysaccharide that forms a linear chain structure consisting of repeating units of agarobiose, which is an alternating polymer of D-galactose and 3,6-anhydro-L-galactose linked by alternating β-(1,4) and α-(1,3) bonds. 1 It is widely employed as a gelling agent for microbiological culture media. Agarases are enzymes that hydrolyse the polymer agarose and have potential applications in the food, cosmetic and medical industries for breaking down agar components.…”
Section: Introductionmentioning
confidence: 99%